If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 400 = 2x + 6y + 4z Solving 400 = 2x + 6y + 4z Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 400 + -2x = 2x + 6y + -2x + 4z Reorder the terms: 400 + -2x = 2x + -2x + 6y + 4z Combine like terms: 2x + -2x = 0 400 + -2x = 0 + 6y + 4z 400 + -2x = 6y + 4z Add '-400' to each side of the equation. 400 + -400 + -2x = 6y + -400 + 4z Combine like terms: 400 + -400 = 0 0 + -2x = 6y + -400 + 4z -2x = 6y + -400 + 4z Reorder the terms: -2x = -400 + 6y + 4z Divide each side by '-2'. x = 200 + -3y + -2z Simplifying x = 200 + -3y + -2z
| 4[3+c]=c+4 | | 90t=100+70t | | Y=.25x-2 | | 5-2k=27 | | -8n+4(1+5n)=-6n-1 | | 5h+2c+3h+5h+2c+3h= | | -6.8(x-1.25)=13.6 | | 4n^2+24n=0 | | 6x^4+4x^3+12x^2+4x-2=0 | | 54.9=6(m+2.9) | | 3x-75=27 | | 3n-0.03=(-9) | | 4x-5+2x+5=180 | | 0.6=54x | | Y+6y+y+2c+3c+2y+3c+2c= | | 3a+6y-89b= | | 2(r+9)=29 | | 2x+35-14x=26x+35 | | 7x+3=7(x-4) | | 0.31+0.15(x-1)+2.12=2.73 | | 8x^7-40x^5=0 | | 4h-10=2h-4 | | 5g+2(-3+3g)=1-g | | 4(6x-30)=72 | | f(5+5)=f(5)+f(5) | | 10y=7y+21 | | x^2+y^2=90 | | 2(11+2x)+2(19+2x)=76 | | (x+4)2+112=0 | | f(5+5)= | | abs(10+2x)=16 | | -6X+-36+2=-6x+-3 |